THE INFLUENCE OF ENTREPRENEURSHIP SPIRIT AND ENTREPRENEURSHIP VALUE ON BUSINESS SUCCESS IN TEMBUNG BERSATU PERCUT SEI TUAN - Dahrul Siregar; Hesti Sabrina (Jurnal Ekonomi, 2022)
The purpose of this study is to determine and analyze the influence of entrepreneurial spirit and entrepreneurial values ​​​​on business success in UKM Tembung Bersatu, Percut Sei Tuan District. The research method used is exploratory research, where variables are measured using a Likert scale. Methods of data collection are done by interview (interview), with a list of statements (Questioner) and study documentation. The population in this study were all Tembung Bersatu UKM. a total of 40 SMEs. Sampling using the saturated sampling method or better known as a census. In this study, the population was relatively small, namely 40 people. Processing data using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis.